2016
DOI: 10.1080/19443994.2015.1057036
|View full text |Cite
|
Sign up to set email alerts
|

Compaction and relaxation of biofilms

Abstract: A B S T R A C TOperation of membrane systems for water treatment can be seriously hampered by biofouling. A better characterization of biofilms in membrane systems and their impact on membrane performance may help to develop effective biofouling control strategies. The objective of this study was to determine the occurrence, extent and timescale of biofilm compaction and relaxation (decompaction), caused by permeate flux variations. The impact of permeate flux changes on biofilm thickness, structure and stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…Dreszer et al (2014) proposed that two mechanisms govern the biofilm compressibility: a physical compression of the EPS and a chemical EPS consolidation. However in our study, similar hydraulic resistances were measured for the 1st and 2nd compressibility tests, indicating that in our test the compression of the biofilms was entirely reversible These results are in accordance with the study of Vallares Linares et al (2016), who reported that the effect of permeate flux on the hydraulic biofilm resistance is reversible (Vallares Linares et al, 2016).Our results also suggests that chemical EPS consolidation did not occur during the 1st compression test and did not modify the mechanical properties of the biofilms submitted to the 2nd test. The elasticity of biofilms also explains why similar mesoscale physical structures were observed without TMP for the two types of biofilm (Fig.…”
Section: Biofilms Are Compressible Structuressupporting
confidence: 95%
“…Dreszer et al (2014) proposed that two mechanisms govern the biofilm compressibility: a physical compression of the EPS and a chemical EPS consolidation. However in our study, similar hydraulic resistances were measured for the 1st and 2nd compressibility tests, indicating that in our test the compression of the biofilms was entirely reversible These results are in accordance with the study of Vallares Linares et al (2016), who reported that the effect of permeate flux on the hydraulic biofilm resistance is reversible (Vallares Linares et al, 2016).Our results also suggests that chemical EPS consolidation did not occur during the 1st compression test and did not modify the mechanical properties of the biofilms submitted to the 2nd test. The elasticity of biofilms also explains why similar mesoscale physical structures were observed without TMP for the two types of biofilm (Fig.…”
Section: Biofilms Are Compressible Structuressupporting
confidence: 95%
“…Since OCT detects reflection and scattering signals, it is well suited to visualize the overall distribution of particular matter in biofilms. More importantly the main limitation of especially fluorescence imaging is overcome: regions of background signals surrounded by biofilm are identified as voids and cavities (Valladares Linares et al, ; Wagner et al, ). To date none of the biofilm research groups applying OCT have reported if these cavities contain other matters than water (e.g., EPS).…”
Section: Oct In Biofilm Researchmentioning
confidence: 99%
“…This might be an acceptable assumption for an unaltered, sponge‐like biofilm structure containing a high fraction of water. But when the biofilm is compressed (Valladares Linares et al, ) this simplification becomes to some extend obsolete the more water is released. However, Ratheesh Kumar et al () estimated the refractive index of biofilm during a cultivation by means of a swept‐source OCT. Their measurements revealed a refractive index of n1.355 confirming the general simplification made in most studies.…”
Section: Oct In Biofilm Researchmentioning
confidence: 99%
See 2 more Smart Citations